Pengembangan Bahan Ajar Leaflet Pada Materi Menganalisis Teks Anekdot Kelas X SMA Negeri 8 Medan Tahun Pembelajaran 2023/2024 - Ade Siska (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study is to find out the process of developing material for analyzing anecdotal texts for class X of SMA Negeri 8 Medan for the 2023/2024 Academic Year. To find out the form of teaching material anecdotal texts as a result of observation on leaflets in class x of high school. And to find out the feasibility of the products produced. And to be able to make leaflet teaching materials in Indonesian lessons on the subject of anecdotal texts, analyze the feasibility of leaflets for Indonesian learning teaching materials in texts Anecdote of class x SMA Negeri 8 Medan. The research method used (Research and development) using the procedure from Borg and Gel by (Sugiyono). The development stage with data, designing development products, conducting validation, revisions, products, and small-scale trials. The development was validated by three validators, namely material experts with an assessment of 68% in the feasible category, validation of design experts with an achievement of 59% in the feasible category, and scale feasibility test as many as 15 students with an average assessment of 92% which means that it is included in the very feasible category. The material development process is carried out to add several contributions in developing the material that is carried out to increase the contribution in developing anecdotal text material from existing observations to be better. From the results of the overall research on the feasibility assessment of teaching materials that have been presented, the teaching materials are in the form of leaflets in the anecdotal text material of class x SMA Negeri 8 Medan has a very feasible (valid) category so that it can be used as this research for further research reference.